Physical, Optical, and Spectroscopic Studies on MgO-BaO-B2O3 Glasses. (24th December 2013) - Samdani,; Shareefuddin, Md.; Ramadevudu, G.; Rao, S. Laxmi Srinivasa; Narasimha Chary, M.
Abstract : The mixed alkaline effect in double alkaline borate glasses MgO-BaO-B2 O3 containing small proportions of copper oxide (CuO) has been studied. The glass samples are characterized by optical absorption, electron paramagnetic resonance (EPR), and Fourier transform infrared spectroscopy (FTIR). A red shift in optical absorption peaks with increasing MgO (decreasing BaO) concentration has been observed. The values of "g " tensor and hyperfine "A " tensor have shown inflections with glass composition. The number of spins ( N ) and paramagnetic susceptibility (χ ) also exhibited mixed alkaline effect. The broadening of glass network with increase in MgO concentration is found from the FTIR spectra. Interestingly both density and molar volume have shown decreasing trend with glass composition. The optical band gaps exhibited a nonlinear compositional dependence. As expected, the glass samples possessed higher values of optical basicity (Λ), molar electronic polarizability (α m ), and Urbach energy (ΔE ).